Sistem Pemilihan Program Studi - Pratama, Muhammad Yogi; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Technological developments facilitate human’s performance in determining decisions, one of these technologies is a prediction system that predicts future decisions. An example of prediction system of study programs. Choosing a study program is a decision-making process that requires consideration for prospective new students, because the majors to be chosen are very diverse. Based on these conditions, Prediction System of a Study Program Selection is built. The prediction system is designed using PHP Hypertext Preprocessor programming language which inserted into HTML document to run a web-based system on server side to get dynamic processing forms. Every created page will change according to user’s inputs. All processes in server are not visible for clients. Data storage uses My Structured Query Language (MySQL) server database as an interactive language in managing data. Each client can make a request by typing a specific SQL statement so that the MySQL server will respond by providing the requested information and it will appear on the client side. This system can provide references and recommendations for Prospective New Students in choosing the Undergraduate Study Program to be taken later. After testing system, results of the system carried out. It can be concluded that Prediction System of Study Program Selection can make easier to provide references and recommendations for Prospective New Students in choosing the right Study Programs through web browser. Keywords : Study Program, Study Program Selection System, PHP, MySql, Web.